Arteriovenous Malformation in Temporal Lobe Presenting as Contralateral Ocular Symptoms Mimicking Carotid-Cavernous Fistula - Fadzillah Mohd-Tahir; Ishak Siti-Raihan; W. H. Wan Hazabbah (Case Reports in Ophthalmological Medicine)
Aim. To report a rare case of arteriovenous malformation in temporal lobe presenting as contralateral orbital symptoms mimicking carotid-cavernous fistula. Method. Interventional case report. Results. A 31-year-old Malay gentleman presented with 2-month history of painful progressive exophthalmos of his left eye associated with recurrent headache, diplopia, and reduced vision. Ocular examination revealed congestive nonpulsating 7 mm exophthalmos of the left eye with no restriction of movements in all direction. There was diplopia in left lateral gaze. Left IOP was elevated at 29 mmHg. Left eye retinal vessels were slightly dilated and tortuous. CT scan was performed and showed right temporal arteriovenous malformation with a nidus of 3.8 cm × 2.5 cm with right middle cerebral artery as feeding artery. There was dilated left superior ophthalmic vein of 0.9 mm in diameter with enlarged left cavernous sinus. MRA and carotid angiogram confirmed right temporal arteriovenous malformation with no carotid-cavernous fistula. Most of the intracranial drainage was via left cavernous sinus. His signs and symptoms dramatically improved following successful embolisation, completely resolved after one year. Conclusion. Intracranial arteriovenous malformation is rarely presented with primary ocular presentation. Early intervention would salvage the eyes and prevent patients from more disaster morbidity or fatality commonly due to intracranial haemorrhage.